Coherent Conversion Between Microwave and Optical Photons—An Overview of Physical Implementations. Issue 1 (12th December 2019) - Lambert, Nicholas J.; Rueda, Alfredo; Sedlmeir, Florian; Schwefel, Harald G. L.
Abstract: Quantum information technology based on solid state qubits has created much interest in converting quantum states from the microwave to the optical domain. Optical photons, unlike microwave photons, can be transmitted by fiber, making them suitable for long distance quantum communication. Moreover, the optical domain offers access to a large set of very well‐developed quantum optical tools, such as highly efficient single‐photon detectors and long‐lived quantum memories. For a high fidelity microwave to optical transducer, efficient conversion at single photon level and low added noise is needed. Currently, the most promising approaches to build such systems are based on second‐order nonlinear phenomena such as optomechanical and electro‐optic interactions. Alternative approaches, although not yet as efficient, include magneto‐optical coupling and schemes based on isolated quantum systems like atoms, ions, or quantum dots. Herein, the necessary theoretical foundations for the most important microwave‐to‐optical conversion experiments are provided, their implementations are described, and the current limitations and future prospects are discussed. Abstract : Spatially separated quantum technologies will need to communicate using optical channels, rather than at the microwave frequencies which often correspond to the energy scales associated with superconducting qubits. Techniques for coherent transduction between the two frequency regimes are therefore an active and important area of research. Herein, current experimental approaches for microwave up‐conversion to optical frequencies are reviewed.